Caracterização da produção espacial missioneira itinerante dos frades capuchinhos da Prefeitura da Penha do Recife (1841-1889) - Almeida, Reberth Emannuel Rocha (2019)
In 1841, the old Capuchin hospice of Nossa Senhora da Penha in Recife saw the arrival of the first group of Italian friars who would start a new cycle of the presence of such a Franciscan religious Order in Brazil. In discontinuous cycles, the Capuchin presence on Brazilian soil has been marked remotely since the French invasions of Maranhão in the 17th century, and also appeared in the 17th, 18th and the first half of the 19th century, grouped in two other moments: a cycle composed of the presence of Breton friars and another composed by the presence of Italian friars. With a small network of houses (hospices), but a wide network of indigenous missionary settlements coordinated by them, the Capuchins initially extended their activities mainly in the territory corresponding to the present Brazilian Northeast - below and above the São Francisco river - contributing, alongside other Orders, to the establishment of a new social order which included not only the Christianization of the native peoples but also the insertion of new forms of space. Based on a Franciscan reformist mystique in which it was important to walk, in Brazil the friars first concentrated their spatialization on the central regions of the territory where they worked in the formatting and direction of indigenous villages/fixed missions. However, as they entered the 18th century (during the first Italian cycle), with the consolidation of Christianity and new ways of occupying the land, the friars began to act also through another device, that is, the so-called itinerant missions. Unlike the fixed missions (indigenous villages), in the itinerant missions the friar was not fixed for long periods in one place, but used to walk from place to place, staying for shorter intervals in each one, in order to meet the religious needs of these already Christianized places (catechesis, distribution of sacraments, etc.). In the 18th century, in the midst of the itinerant missions, at certain times, meeting religious needs implied building, being one of the best known legacies of that period the Monte Santo of Bahia, one of the scenarios of the War of Canudos. However, this work focuses especially on the first five decades of the second Italian cycle of the Capuchin friars in Penha of Recife opened from the reentry of these religious in Pernambuco and the resumption of the old hospice and prefecture in 1841. In this new cycle, the friars of Penha redirected and concentrated their activities on itinerant missions, traversing and building among several localities of the former provinces of Pernambuco, Alagoas, Paraíba, Rio Grande do Norte and Ceará. In addition to other researches that have advanced on the studies of the Franciscan / Capuchin legacies in different areas, this master’s dissertation concentrates on understanding the spatial production of the itinerant missions of the friars of Penha of Recife between 1841 and 1889, investigating the dynamics which involved the acts of the itinerant walking, sacrificial building and leaving missionary legacies that still have repercussions in the social and landscape formation of the Brazilian Northeast. For this end, several different sources in their contents and their temporalities (such as memoirs, letters, books, newspapers, images and visits to some of the sites produced during the missions) were analyzed in order to understand the spirituality and the incorporation of the friars and their itinerant missions by governments and populations and consequently the repercussions of these things in the space.